Scope and limitations of palladium-catalyzed cross-coupling reactions with organogold compounds - Hashmi, A. Stephen K.; Döpp, René; Lothschütz, Christian; Rudolph, Matthias; Riedel, Dominic; Rominger, Frank (Advanced synthesis & catalysis, 2010)
Five different alkenylgold(I) phosphane complexes were prepared and then investigated in [1,1′-bis(diphenylphosphino)ferrocene]palladium(II) dichloride-catalyzed cross-coupling reactions with different aryl halides, heterocyclic halides, an alkenyl halide, an alkynyl halide, allylic substrates, benzyl bromide and an acid chloride. With regard to the halides, the iodides were highly reactive, bromides or chlorides gave significantly reduced yields or failed, allylic acetates failed, too. The cross-coupling partners contained a number of different functional groups, while free carboxylic acids did not deliver cross-coupling products and o,o-disubstituted arenes failed as well, a broad range of other functional groups like nitro groups, nitrile groups, ester groups, α,β-unsaturated ester groups and lactones, aldehydes, alkoxy groups, pyridyl groups, thienyl groups, unprotected phenols and anilines, even aryl azides were tolerated. The structures of one alkenylgold(I) species and of four of the cross-coupling products were proved by crystal structure analyses.